Emotional Quotient Dan Persepsi Tentang Profesi Asisten Apoteker Dapat Meningkatkan Prestasi Belajar Farmasetika Pada Mahasiswa Prodi DIII Farmasi (Emotional Quotient And Perception On Assistant Pharmacist Profession Increase Pharmaceutical Learning Ach - Sri Saptuti Wahyuningsih (Indonesian Journal on Medical Science, 2015)
Abstract: Pharmaceutical learning achievement is closely related to the perception and Emotional Quotient. Perception on Assistant Pharmacist Profession is student’s understanding in interpreting the Assistant Pharmacist Profession. Emotional quotient is the student’s ability in managing self-emotion during attending learning process up to education completion. The purpose of this study was analyze the relationship of Perception on Assistant Pharmacist Profession and emotional quotient to pharmaceutical learning achievement in the students of Pharmacy Undergraduate Study Program of Poltekkes Bhakti Mulia of Sukoharjo. This study was an analytical observational quantitative research with cross sectional approach. The population in the research was 82 students. The sample was 65 students with the sampling technique used was Proportionate Random Sampling. The data analysis was conducted using prerequisite analysis including normality, linearity and independency test, followed with first and second hypothesis tests with Product Moment, and third hypothesis test with a multiple regression. There was a positive significant relationship between Assistant Pharmacists Profession and learning achievement at significance level = 0.001 and effective contribution of 18.26%. There was a positive significant relationship between emotional quotient and learning achievement at significance level = 0.001 and effective contribution of 12.15%. There was a positive significant relationship of Perception on Assistant Pharmacist Profession and emotional quotient simultaneously to pharmaceutical learning achievement at significance level = 0.001 and effective contribution of 30.41%. In Conclusion, There was a positive significant relationship of Perception on Assistant Pharmacist Profession and emotional quotient to pharmaceutical learning achievement.Keywords: Emotional Quotient, Learning Achievement, Assistant Pharmacists Profession. Abstrak: Prestasi belajar farmasetika berhubungan erat dengan persepsi dan kecerdasan emosi. Persepsi tentang Profesi Asisten Apoteker adalah pemahaman mahasiswa dalam menginterpretasikan tentang Profesi Asisten Apoteker. Kecerdasan emosi adalah kemampuan mahasiswa dalam mengelola emosi pada dirinya selama mengikuti proses pembelajaran sampai selesai pendidikan. Tujuan penelitian ini adalah untuk menganalisis hubungan persepsi tentang Profesi Asisten Apoteker dan kecerdasan emosi dengan prestasi belajar farmasetika pada  mahasiswa Prodi DIII Farmasi di Poltekkes Bhakti Mulia Sukoharjo. Penelitian ini merupakan penelitian kuantitatif Analitik Observasional dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah 82 mahasiswa.  Sampel 65 mahasiswa dengan teknik pengambilan sampel menggunakan Teknik Proportionate Random Sampling. Analisis data dengan uji prasyarat yaitu uji normalitas, uji linearitas dan uji independensi, kemudian dilanjutkan dengan uji hipotesa pertama dan kedua dengan Product Moment, uji hipotesa ketiga dengan korelasi regresi ganda. Ada hubungan positif yang signifikan antara persepsi tentang Profesi Asisten Apoteker dengan prestasi belajar dengan nilai signifikansi = 0,001 dan sumbangan efektif sebesar 18,26%. Ada hubungan positif yang signifikan antara kecerdasan emosi dengan prestasi belajar dengan nilai signifikansi = 0,001 dan sumbangan efektif sebesar 12,15%. Ada hubungan positif yang signifikan antara persepsi tentang Profesi Asisten Apoteker dan kecerdasan emosi secara bersama-sama dengan prestasi belajar farmasetika dengan nilai signifikansi = 0,001  dan sumbangan efektif sebesar 30,41%. Simpulannya, terdapat hubungan positif yang signifikan antara persepsi tentang Profesi Asisten Apoteker dan kecerdasan emosi dengan prestasi belajar farmasetika. Kata kunci: Kecerdasan Emosi, Prestasi Belajar, Profesi Asisten Apoteker.